1999
DOI: 10.1074/jbc.274.21.14541
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Human Lipoprotein A-I

Abstract: The two main competing models for the structure of discoidal lipoprotein A-I complexes both presume that the protein component is helical and situated around the perimeter of a lipid bilayer disc. However, the more popular "picket fence" model orients the protein helices perpendicular to the surface of the lipid bilayer, while the alternative "belt" model orients them parallel to the bilayer surface. To distinguish between these models, we have investigated the structure of human lipoprotein A-I using a novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
117
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(122 citation statements)
references
References 30 publications
4
117
0
1
Order By: Relevance
“…The crystal structure showed a tetramer of highly α-helical apoA-I molecules arranged in a ring-shaped complex with no evidence of hairpin turns that would be prevalent in the picket fence. The belt model picked up more support with methodologically updated IR experiments performed by Koppaka et al (1999) that contradicted the earlier IR studies supporting the picket fence in rHDL discs. Over the next few years, several laboratories reported results that supported the belt orientation using methodologies like fluorescence energy transfer (Li et al 2000) and lipid-based fluorescence quenching (Panagotopulos et al 2001).…”
Section: Introduction/brief Historymentioning
confidence: 70%
“…The crystal structure showed a tetramer of highly α-helical apoA-I molecules arranged in a ring-shaped complex with no evidence of hairpin turns that would be prevalent in the picket fence. The belt model picked up more support with methodologically updated IR experiments performed by Koppaka et al (1999) that contradicted the earlier IR studies supporting the picket fence in rHDL discs. Over the next few years, several laboratories reported results that supported the belt orientation using methodologies like fluorescence energy transfer (Li et al 2000) and lipid-based fluorescence quenching (Panagotopulos et al 2001).…”
Section: Introduction/brief Historymentioning
confidence: 70%
“…26 The discoidal HDL particle involves phospholipid layer oriented parallel to the ApoA1 helices that wrap the particle edge like a double belt. 41 The elongated helical structure is punctuated by kinks at proline residues. 42 In the HDL disk, chemical cross-linking experiments showed that the central helical portion (a.a. 121-142) of one ApoA1 molecule is adjacent to the similar region of its counterpart.…”
Section: Apoa1 Structure In Discoidal Hdl Particlesmentioning
confidence: 99%
“…Since then, there have been two studies on true lipid-containing particles that specifically addressed the orientation of apoA-I helices in relation to phospholipid acyl chains. The first was attenuated IR experiments by Koppaka et al (35) that clearly supported the belt model in hydrated particles. More recently, this methodology demonstrated that apoE (36) and apoA-II (37) also adopt a belt-like orientation in particles of similar morphology.…”
Section: Discoidal Hdlmentioning
confidence: 99%